HIV infection among heterosexual travellers attending the Hospital for Tropical Diseases, London. Issue 5 (October 1992) - Hawkes, S; Malin, A; Araru, T; Mabey, D
Abstract : OBJECTIVE–To determine the prevalence of HIV infection in travellers attending the Hospital for Tropical Diseases, London, and to assess correlates and behavioural risk factors for infection. DESIGN–All patients tested for HIV infection during a 28-month period were included. Information was obtained from clinical records and standardised serological request forms. SETTING–Hospital for Tropical Diseases, London, UK. SUBJECTS–298 patients (in-patient and out-patient) were tested. RESULTS–258 of those tested were exclusively heterosexual and not injecting drug users. 5.4% of these were HIV-1 antibody positive. Rates in those originating from the UK and those from outside the UK were 1.8% and 33.2% respectively. Most non-UK citizens were symptomatic when tested; UK citizens were generally tested as part of a routine screening, therefore the two groups are not comparable. Rates of risk behaviour were high in both groups. CONCLUSION–The rate of HIV infection in heterosexual travellers was 5.4%. Amongst UK citizens the rate was 1.8%. All travellers should be made aware of the potential risk of acquiring HIV infection through sexual contact.